Outer Membrane Proteome Analysis of Indian Strain of Pasteurella multocida Serotype B:2 by MALDI-TOF/MS Analysis - A. Prasannavadhana; Santosh Kumar; Prasad Thomas; Laxmi Narayan Sarangi; Santosh Kumar Gupta; Adyasha Priyadarshini; Viswas Konasagara Nagaleekar; Vijendra Pal Singh (The Scientific World Journal)
Identification of outer membrane proteins (OMPs) is important to understand the bacteria structure and function, host-pathogen interaction, development of novel vaccine candidates, and diagnostic antigens. But till now the key antigens of P. multocida B:2 isolate causing haemorrhagic septicaemia (HS) in animals are not clearly defined. In this study, P52 strain of P. multocida serotype B:2 was grown in vitro under iron-rich and iron-limited condition. The OMPs were extracted by sarkosyl method followed by SDS-PAGE and the proteins were identified by MALDI-TOF/MS analysis. In total, 22 proteins were identified, of which 7 were observed exclusively under iron-limited condition. Most of the high molecular weight proteins (TbpA, HgbA, HgbB, HasR, IroA, and HemR) identified in this study were involved in iron acquisition. Some hypothetical proteins (HP-KCU-10206, HP and AAUPMB 08244, HP AAUPMB 21592, HP AAUPMB 19766, AAUPMB 11295) were observed for the first time in this study which could be unique to serotype B:2. Further functional in vivo study of the proteins identified are required to explore the utility of these proteins in developing diagnostics and vaccine against HS.